Understanding the nature of landslides through detailed geomorphological mapping on the Sumbing Volcanic Landscape, Java Island, Indonesia - Elok Surya Pratiwi; Su-min Shen; Junun Sartohadi (Journal of Maps)
A 1:2,500-scale geomorphological map was created to illustrate the landslide characteristics on the southern flank of the Sumbing Volcanic Landscape (SVL), Java Island, Indonesia. High-resolution LiDAR Digital Terrain Model (DTM), Global Navigation Satellite System (GNSS) data, Unmanned Aerial Vehicle (UAV)-based aerial photographs, and field surveys were integrated to enable detailed landform interpretation of post-volcanic mass wasting processes. Landslides were classified by type, activity level, and origin. Additionally, morphometric analysis, including slope and area measurements, was conducted. Through this detailed geomorphological mapping process, it reveals that most recent landslides have developed within relict landslides, which were previously overlooked. It also detects smaller, more hazardous landslides caused by human activities, in addition to those triggered by natural forces. This study represents the first large-scale geomorphological mapping effort integrating high-resolution datasets in Indonesia’s dormant volcanic landscapes. It will enhance understanding of landslide characteristics and will support disaster management strategies.